2017
DOI: 10.18621/eurj.332008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of obesity on functional capacity, anxiety and daily life activities in patients with coronary artery disease and phase II cardiac rehabilitation

Abstract: Objective. The aim of our study was to investigate the effect of cardiac rehabilitation (CR) program on obese and non-obese patients with coronary artery disease. Methods. The records of 60 coronary artery disease patients aged between 18-75 years, who were included in CR were evaluated. Of the study subjects, 20 had undergone coronary artery bypass grafting (CABG) and 40 had undergone percutaneous coronary intervention (PCI). The patients were divided into two groups by body mass index (BMI), with Group I bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Similarly, another RCTs demonstrated significant reductions in LDL-C and systolic BP values [70]. Kasapoglu Aksoy et al [77] found that CR was found to be effective and safe in terms of functional capacity, daily life activities and anxiety in both obese and non-obese patients. In addition, one RCT that addressed ≥ 6 CVD risk factors during CR demonstrated a reduction in overall mortality, but no differences in overall mortality were present in studies that addressed fewer risk factors.…”
Section: Cardioprotective Effect Of Cardiac Rehabilitationmentioning
confidence: 92%
“…Similarly, another RCTs demonstrated significant reductions in LDL-C and systolic BP values [70]. Kasapoglu Aksoy et al [77] found that CR was found to be effective and safe in terms of functional capacity, daily life activities and anxiety in both obese and non-obese patients. In addition, one RCT that addressed ≥ 6 CVD risk factors during CR demonstrated a reduction in overall mortality, but no differences in overall mortality were present in studies that addressed fewer risk factors.…”
Section: Cardioprotective Effect Of Cardiac Rehabilitationmentioning
confidence: 92%